Organizational Design: Decision Rights and Incentive Contracts - Athey, Susan; Roberts, John (American Economic Review, 2001)
Where should decision rights be lodged in organizations? Michael C. Jensen and William H. Meckling (1992) argue that moving a decision away from the inherently best-informed party involves costs in communication and garbling but may lodge it with someone who has better incentives to make good decisions. Generally, however, we expect that incentives are part of the organizational design. Why not just provide incentives to those with the best information so that they make the right decisions? One reason is that the available incentive instruments must serve multiple purposes, and designing them to induce better decisions worsens performance against other organizational objectives. Our experience suggests that this is a common situation in actual organizations: the means available to affect one sort of behavior or decision inevitably affect the incentives governing other choices. Then, the design of incentive schemes and the allocation of decision rights become interlinked. This paper looks at this idea in the specific context of a principal’s problem of inducing agents to provide unobservable effort while also motivating the efficient selection of investments. Each of these problems has been extensively studied in isolation (on inducing effort, see e.g., Bengt Holmstrom [1979] and Holmstrom and Paul Milgrom [1991]; on decisions, see e.g., Eugene F. Fama and Jensen [1983], Milgrom and Roberts [1990a, b], Philippe Aghion and Jean Tirole [1997], Matthias Dewatripont and Tirole [1999]). We thus know that motivating effort is done best by rewarding agents on precise measures of their effort, not necessarily on the total value created in the firm. At the same time, it is clear that getting the right investment choices may require that the decision-makers’ rewards be tied to total value created. The difficulty is that the available measures do not allow doing both. The only available performance measures are aggregates whose component pieces cannot be disentangled, while contracts must be written in advance of learning about investment possibilities. Including many contingencies in the contracts ex ante is impossible, and ongoing renegotiation in every ex post eventuality is prohibitively costly. More formally, we assume that it is not possible to contract on investment projects, nor can the principal bargain with the agents over the adoption of these projects once they are identified. Instead, returns to projects are reflected in the performance measures available for use in the effort-incentive contracting. Then the incentives for effort and for decisions are inextricably tied together. In this framework, we explore the interactions among the design of jobs and assignment of individuals to tasks, the shape and intensity of effort incentives, and the allocation of authority over project selection. We argue that it may indeed be optimal to assign decisions rights to someone other than the best-informed party. An authority-based hierarchy then emerges endogenously, with some agents being given the right to make organizational decisions over projects that others discovered. Moreover, as in Herbert Simon (1951), those in authority will make the decisions in a self-interested way. Simon emphasized that this † Discussants: Michael Riordan, Columbia University; Bengt Holmstrom, Massachusetts Institute of Technology; W. Bentley MacLeod, University of Southern California.